Effect of Prior Symptomatic Dengue Infection on Dengue Haemorrhagic Fever (DHF) in Children. (3rd June 2021) - Ranawaka, Randula; Jayamanne, Chamara; Dayasiri, Kavinda; Samaranayake, Dinuka; Sandakelum, Udara; Hathagoda, Wathsala; Dissanayake, Ruwangi; Wickramasinghe, Pujitha
Abstract : Pathogenesis of dengue haemorrhagic fever is not fully understood, but it is thought that there is antibody enhancement during the secondary infection, which causes severe dengue haemorrhagic fever (DHF). Therefore, patients who have DHF should have a documented history of symptomatic dengue infection in the past. A retrospective descriptive-analytical study was conducted at the University Paediatric Unit at Lady Ridgeway Hospital for Children, Colombo, Sri Lanka. All children who had fulfilled the criteria for DHF admitted to the unit from April 2018 to September 2018 were recruited into the study. Relevant data were collected from bed head tickets. One hundred and eighty-four children were included in the final analysis. Thirty-three (17.9%) had a past history of documented symptomatic dengue infection, while 82.1% did not have a documented dengue infection. Twelve patients had dengue shock syndrome, and none of them had previously documented symptomatic dengue fever. Dextran was used in 96 patients in the critical phase. Twelve (42%) patients with past documented symptomatic dengue fever needed dextran while 84 (54.9%) patients without a documented past history of dengue fever needed dextran. In our clinical observation, we noticed that children with DHF mostly did not have a documented symptomatic prior dengue infection, while those with a documented symptomatic prior infection had a milder subsequent illness. In fact, the majority (82.1%) of patients with DHF did not have documented previous symptomatic dengue infection. It was also observed that the clinical course of subsequent dengue infection was less severe in patients with previously documented symptomatic dengue fever. This finding should be further evaluated in a larger scale study minimizing the all-confounding factors. This fact is more important in selecting recipients for vaccines against the dengue virus, which are supposed to produce immunity against the virus without causing the severe disease.